Mapping Non-Prescription Pre-Session Support across Psychedelic Substances - Rubenstein, Elias (International Journal of Independent Research Studies, 2026)
Psychedelic preparation is commonly discussed through screening, psychological readiness, set, setting, therapeutic support, and integration planning. In clinical-adjacent, retreat, ceremonial, and harm-reduction contexts, however, non-prescription pre-session supports are also used or discussed before psychedelic sessions. These practices may involve nutrients, botanicals, amino acids, cannabinoids, terpenes, hydration strategies, sleep-related agents, gastrointestinal supports, or non-ingestive procedures such as PC6 acupoint stimulation and orientation scripts. At present, they are often described as informal advice, product-specific recommendations, or commercial stacks rather than as researchable categories. This article maps non-prescription pre-session support practices across psychedelic substances and organizes them into a research taxonomy based on intended target domain, inclusion rationale, psychedelic context, evidence boundary, and interaction burden. It does not propose supplement stacks, dosing rules, treatment recommendations, medication-discontinuation advice, or clinical protocols. Individual agents are mentioned only as illustrative examples of broader categories and are linked to evidence boundaries. The purpose is to make such practices documentable and comparable for future research while avoiding premature clinical or commercial translation.